A prática educativa à luz da Pedagogia Social e da Psicologia Social Comunitária: estudo do programa integração AABB Comunidade - Graciani, Juliana Santos (2015)
The research aimed to reflect on the educational practice by analyzing the Plans Pedagogical Integration Program of Social Educators Activities AABB Community in light of the foundations of Social Pedagogy and Social Community Psychology, assuming that the theoretical aspects and methodological these can contribute to the understanding of this social project. We use this research, qualitative methodology and the technical procedure of document analysis, referring to the activities of Pedagogical Plans sent to the competition 2013. Agenda Case For the research was requested to accept the use of authority term of the Contest data and for the choice of the criterion of educational practices we chose to analyze all 105 experiments sent. The analysis was performed from the three categories of Community Social Psychology (Active Participation, Strengthening Affective and Community Impact Bonds) and the four fields of Social Pedagogy (Epistemological, sociopedagogical, sociocultural and sociopolitical). As for the results obtained, the Socio-cultural domain and Active Participation category were those most stood out, soon after, the sociopolitical domain, and finally simultaneously with the same score, the Epistemological and socio-pedagogical fields of Social Pedagogy and the categories of strengthening Affective Links and Community Impacts, prevailed in second and third place in the Community Social Psychology. We conclude that the educational practices encouraged the artistic actions, cultural, sports, environmental, social and educational complementation and citizenship, favoring the personal, family and community exercise of educational proposals with the changes in the reality experienced individually and in society, aspects that the transversalizam theoretical and practical foundations of the relationship between science Social Pedagogy and Social Community Psychology front of the educational practice